Pengaruh Profitabilitas Dan Kompleksitas Operasi Pada Audit Delay Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Putra, Adhika Candra; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi, 2019)
This study aims to examine the effect of profitability and operational complexity on audit delay and test the effect of size of the company as moderating variable. This research was conducted at mining companies listed on Indonesia Stock Exchange in 2013-2017 which were accessed through www.idx.co.id. The sampling method used was purposive sampling with a total sample of 50. The analysis technique used in this study was Multiple Linear Regression to examine the direct effect of profitability and operational complexity on audit delay and Moderated Regression Analysis to test firm size as moderating influence profitability and operational complexity in audit delay. The results showed that profitability had negative effect on audit delay. The operational complexity has no effect on audit delay. The size of the company strengthens the negative effect of audit delay on profitability. Firm size is not able to moderate the influence of operational complexity on audit delay. Keywords :  Profitability, complexity of company operation, firm size, audit delay